Scaffolding as a metaphor in disciplinary content and in multimedia architecture: A CD-ROM on Building Understandings in Literacy and Teaching - Love, Kristina (Australasian Journal of Educational Technology, 2002)
This paper outlines key decisions that were made in the design of a multimedia resource (a CD-ROM entitled 'BUILT') that develops preservice teachers' understandings about language, literacy and teaching. A major consideration in the design process was that the concept of scaffolding, central to the instructional content regarding learning and teaching through language, should also be operationalised in the instructional design of the CD-ROM. A second consideration was that preservice teachers be provided with authentic materials for observation, analysis and reflection and thus the operating structure of the CD-ROM conforms to the conditions for situated learning. A final consideration was that the hypermedia form of the resource be suitable to meet the needs of a variety of cohorts of users.